2018
DOI: 10.3390/ijerph15040647
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Time-Stratified Case-Crossover Design to Explore the Effects of Air Pollution and Season on Childhood Asthma Hospitalization in Cities of Differing Urban Patterns: Big Data Analytics of Government Open Data

Abstract: Few studies have assessed the lagged effects of levels of different urban city air pollutants and seasons on asthma hospitalization in children. This study used big data analysis to explore the effects of daily changes in air pollution and season on childhood asthma hospitalization from 2001 to 2010 in Taipei and Kaohsiung City, Taiwan. A time-stratified case-crossover study and conditional logistic regression analysis were employed to identify associations between the risk of hospitalization due to asthma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 26 publications
(32 reference statements)
1
17
0
1
Order By: Relevance
“…Although Weber et al [16] did not find warm-cold season differences, others have found season differences in the contribution of PM 2.5 to respiratory-cardiovascular chronic disease hospital events [12,59,[74][75][76][77][78][79]. Warm vs. cold season differences were evaluated in this study.…”
Section: Seasonmentioning
confidence: 60%
“…Although Weber et al [16] did not find warm-cold season differences, others have found season differences in the contribution of PM 2.5 to respiratory-cardiovascular chronic disease hospital events [12,59,[74][75][76][77][78][79]. Warm vs. cold season differences were evaluated in this study.…”
Section: Seasonmentioning
confidence: 60%
“…The article reflected the results of an investigation into the interiors of buildings in the city of Beijing. In the same context, there were several other studies focused on air pollution monitoring by Big Data analysis techniques [4,5,[12][13][14][15][16][17][18]. Some focused specifically on vehicular congestion [19][20], while others examined the adverse effects that occur in humans, such as infertility [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The big data concept refers to the processing of large volumes of data by developing mathematical algorithms, in order to establish relationships between data (structured, unstructured and semi-structured) and to determine behavioral patterns that predict trends for improving decision-making. Analysis of big data using traditional methods would take too long and would be very expensive to upload them to a relational database for analysis, and few studies have analyzed this technology in patients with asthma [19][20][21][22][23][24][25][26]. Savana is able to analyze and interpret the plain free text contained in electronic medical records, regardless of the electronic system in which they operate, in order to conduct predictive analyses without the use of classical statistical methods, and to compare them with the descriptive analysis of prevalence and the prospective analysis of the course of patients in the first part of the study, which will be considered the gold standard against which the tool will be compared.…”
Section: Introductionmentioning
confidence: 99%